PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA CHEESE CHICKEN PALEM - Intan Dewi Febriani; Surono Surono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to identify the effect of product quality, price perception, and service quality to improve purchasing decisions on Cheese Chicken Taman Palem. The author took a sample of 130 respondents using the Partial Least Square (PLS) analysis method using the SmartPLS 3 application. This research was conducted using quantitative and descriptive methods, describing the relationship between phenomena studied systematically, factually and accurately. The population in this study are consumers who have visited and purchased Cheese Chicken Palem products in the last 3 months, respondents are domiciled in Jakarta. Based on the results of the study, it is known that all product quality variables, price perceptions and service quality have a significant effect on purchasing decisions on Cheese Chicken Palem as a whole, with a 70% compatibility research model (Model Fit). The results of this study contribute to efficiency in choosing factors or methods of this business unit to improve consumer purchasing decisions in the culinary business.